2021
DOI: 10.3390/ijms222313173
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Regulation of Cellular Senescence

Abstract: Cellular senescence entails a state of an essentially irreversible proliferative arrest in which cells remain metabolically active and secrete a range of pro-inflammatory and proteolytic factors as part of the senescence-associated secretory phenotype. There are different types of senescent cells, and senescence can be induced in response to many DNA damage signals. Senescent cells accumulate in different tissues and organs where they have distinct physiological and pathological functions. Despite this diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(135 citation statements)
references
References 365 publications
1
131
0
3
Order By: Relevance
“…When the DNA damage response (DDR) is prolonged, it promotes senescence [4]. Further known mechanisms underlying senescence are: (1) persistent DDR activation at telomeres, the ends of chromosomes, which is sufficient to activate replicative cell senescence [8]; (2) oncogene activation partly via reactive oxygen species (ROS) production, determining hyperproliferation and altered DNA replication profiles [4,8]; (3) cell cycle arrest by upregulation of p21 and p16 [9]; (4) mitochondrial abnormalities with an increase in ROS synthesis and impairment in biogenesis and mitophagy [10]; (5) induction to resistance to apoptosis by upregulation of the antiapoptotic proteins [10]; (6) metabolic changes determined by senescence-associated-β-galactosidase (SA-β gal) accumulation along with the increase in cellular lysosomal content [10]; (7) large-scale chromatin reorganization occurring with the generation of senescence-associated heterochromatin foci, which suppress transcription of pro-proliferation genes [10]; (8) secretion of pro-inflammatory cytokines, chemokines, proteases, and growth factors that influence the neighbouring cells (SASP profile); (9) morphological alterations including cellular flattening and enlargement [10]; (10) post-transcriptional regulatory pathways taking place at different levels: through the action of mRNA-binding proteins (RBPs) and noncoding RNAs [11][12][13][14]; through a dysregulated splicing factor expression [12,15]; and through N6-methyladenosine (m6A) processes with specific m6A-binding proteins [14].…”
Section: Introductionmentioning
confidence: 99%
“…When the DNA damage response (DDR) is prolonged, it promotes senescence [4]. Further known mechanisms underlying senescence are: (1) persistent DDR activation at telomeres, the ends of chromosomes, which is sufficient to activate replicative cell senescence [8]; (2) oncogene activation partly via reactive oxygen species (ROS) production, determining hyperproliferation and altered DNA replication profiles [4,8]; (3) cell cycle arrest by upregulation of p21 and p16 [9]; (4) mitochondrial abnormalities with an increase in ROS synthesis and impairment in biogenesis and mitophagy [10]; (5) induction to resistance to apoptosis by upregulation of the antiapoptotic proteins [10]; (6) metabolic changes determined by senescence-associated-β-galactosidase (SA-β gal) accumulation along with the increase in cellular lysosomal content [10]; (7) large-scale chromatin reorganization occurring with the generation of senescence-associated heterochromatin foci, which suppress transcription of pro-proliferation genes [10]; (8) secretion of pro-inflammatory cytokines, chemokines, proteases, and growth factors that influence the neighbouring cells (SASP profile); (9) morphological alterations including cellular flattening and enlargement [10]; (10) post-transcriptional regulatory pathways taking place at different levels: through the action of mRNA-binding proteins (RBPs) and noncoding RNAs [11][12][13][14]; through a dysregulated splicing factor expression [12,15]; and through N6-methyladenosine (m6A) processes with specific m6A-binding proteins [14].…”
Section: Introductionmentioning
confidence: 99%
“…Gitenay and his colleagues also found that senescent human epithelial cells displayed a declined glucose uptake, lactate production as well as lower ATP levels [ 53 ]. Inconsistent herewith, it was reported that cell senescence is associated with a progressive and markedly increased rate of glucose metabolism through glycolysis [ 54 , 55 ]. Metabolite analysis revealed that senescent fibroblasts showed a relative increase in glycolysis [ 56 ] and glycolysis-related enzyme activities such as HK, phosphoglycerate kinase (PGK) and PGM were also significantly increased [ 57 ].…”
Section: Discussionmentioning
confidence: 52%
“…At this point, a cell has three primary “options”: 1) it can continue to attempt repair of persisting lesions, albeit likely using error prone alternative DSB repair pathways; 2) the cell cycle arrest becomes permanent, and cells become senescent; or 3) constant damage signaling activates the apoptotic pathways and the cell dies. The induction of senescence and apoptosis is very often cell type dependent, as reviewed in ( Childs et al, 2014 ; Faget, Ren, and Stewart 2019 ; Roger, Tomas, and Gire 2021 ). Additionally, the induction of apoptosis and senescence after exposure to IR can also depend on the innate radiosensitivity of the cell line based on its genetic background ( Balcer-Kubiczek 2012 ; Mirzayans, Andrais, and Murray 2017 ).…”
Section: Cell Fate and Molecular Outcomes After Exposure To High-let Irmentioning
confidence: 99%